Składki zaufania uwzględniające wagę kontraktów - Jasiulewicz, Helena (Credibility Premiums Respecting the Weights of Contracts, 2006)
The paper presents a conception of credibility premiums, which are not well known in the Polish literature on insurance. The Bühlmann-Straub model for setting net premiums for heterogeneous insurance policies is analyzed. Natural and unnatural weights of insurance contracts will be discussed. Next, the influence of the weights on credibility premiums and properties of such predictors will be presented. The theoretical considerations will be ilustrated by a numerical example concerning motor vehicle insurance. This example indicates the potential applications of these concepts in insurance practice.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1108, s. 318-333